A Modified Asymmetric Bouc–Wen Model-Based Decoupling Control of an XY Piezoactuated Compliant Platform with Coupled Hysteresis Characteristics - Xubin Zhou; Weidong Chen; Qing Xiao; Xiangsen Kong; Xingtian Liu; Liping Zhou; Yichong Dong; Quan Zhang (Shock and Vibration)
Due to the inherent hysteresis characteristics of the smart material, the positioning accuracy of the piezo-driven manipulator was always decreased. Especially in multi-degrees-of-freedom (MDOFs) compliant manipulators driven by multismart actuators, the cross-coupled hysteresis among MDOFs decreased the positioning accuracy of such compliant platforms significantly. In this paper, the hysteresis feature identification and coupled hysteresis compensation of a piezo-driven XY manipulator was investigated. To establish the hysteresis characteristics of the piezo-driven manipulator, a modified Bouc–Wen model has been proposed, and a Genetic Algorithm-based Particle Swarm Optimization (GA-PSO) was adopted to recognize the parameters of the model. To improve the output performances of the manipulator, the decoupling controller of the XY micromanipulator was designed, and the driven voltages were modified using the estimated coupling displacements. The experiments validated that the modified Bouc–Wen model featured the ability to present the hysteresis process effectively, and the maximum prediction errors are 0.19 μm and 0.16 μm in the two directions separately. The coupled hysteresis displacement before and after implementing the decoupling controller in the X-direction was reduced from 0.56 μm to 0.15 μm, and the coupling effect is reduced by 73.2%, while in the Y-direction, the coupling effect was also decreased by 72.9%.